-3=2k+9

Simple and best practice solution for -3=2k+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=2k+9 equation:


Simplifying
-3 = 2k + 9

Reorder the terms:
-3 = 9 + 2k

Solving
-3 = 9 + 2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-2k' to each side of the equation.
-3 + -2k = 9 + 2k + -2k

Combine like terms: 2k + -2k = 0
-3 + -2k = 9 + 0
-3 + -2k = 9

Add '3' to each side of the equation.
-3 + 3 + -2k = 9 + 3

Combine like terms: -3 + 3 = 0
0 + -2k = 9 + 3
-2k = 9 + 3

Combine like terms: 9 + 3 = 12
-2k = 12

Divide each side by '-2'.
k = -6

Simplifying
k = -6

See similar equations:

| 7x^2+19x=6 | | 27=-(n-9) | | 8(-4+r)=-16 | | 1=(m-3)-6m^2 | | -2p+8=5-(7p+3) | | -4=-(x+2) | | 4x^2+20x+9y^2-18y-2=0 | | 4x+13-[2x-(4x-12)-5]=2x-12 | | -14x+16=-35+11 | | g/6=20 | | 4+7n=20-3n | | X^2-99x-100=0 | | 5x+12=3x+30 | | -4p-2=42 | | 3(4j+12)=4(4j-12) | | 10(m-7)=110 | | 10(6+x)=150 | | 2(m+12)=7(m-8) | | 10(N-5)=-80 | | 6(3v-7)=3(4v+8) | | 1=-6+7k | | -2+14=0 | | -81=-9(-8+n) | | 3(6+2r)=8r-20 | | 3x+4=4x+3 | | 8t=20t-20 | | -(5y-6)+4(3+5y)y=2 | | 12x-6x^2=0 | | y=-16t^2+63t+4 | | 7x+x+3=42+5x | | 9+7x=23 | | 125=15(x-60)+50 |

Equations solver categories